RUVBL1–RUVBL2 AAA-ATPase: a versatile scaffold for multiple complexes and functions. (April 2021) - Dauden, Maria I; López-Perrote, Andrés; Llorca, Oscar
Graphical abstract: Highlights: RUVBL1–RUVBL2 forms a scaffold in macromolecular complexes such as R2TP and chromatin remodelers. RUVBL1–RUVBL2 ATPase activity is regulated by client-induced motions of DII domains. Conformational changes of an RUVBL2 N-terminal segment control nucleotide binding. Abstract : RUVBL1 and RUVBL2 are two highly conserved AAA+ ATPases that form a hetero–hexameric complex that participates in a wide range of unrelated cellular processes, including chromatin remodeling, Fanconi Anemia (FA), nonsense-mediated mRNA decay (NMD), and assembly and maturation of several large macromolecular complexes such as RNA polymerases, the box C/D small nucleolar ribonucleoprotein (snoRNP) and mTOR complexes. How the RUVBL1–RUVBL2 complex works in such a variety of processes, sometimes antagonistic, has been obscure for a long time. Recent cryo-electron microscopy (cryo-EM) studies have started to reveal how RUVBL1–RUVBL2 forms a scaffold for complex protein–protein interactions and how the structure and ATPase activity of RUVBL1–RUVBL2 can be affected and regulated by the interaction with clients.